If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(9-x)=6(x+6)
We move all terms to the left:
3(9-x)-(6(x+6))=0
We add all the numbers together, and all the variables
3(-1x+9)-(6(x+6))=0
We multiply parentheses
-3x-(6(x+6))+27=0
We calculate terms in parentheses: -(6(x+6)), so:We get rid of parentheses
6(x+6)
We multiply parentheses
6x+36
Back to the equation:
-(6x+36)
-3x-6x-36+27=0
We add all the numbers together, and all the variables
-9x-9=0
We move all terms containing x to the left, all other terms to the right
-9x=9
x=9/-9
x=-1
| (2x-60)+(3x+30)=180 | | 9/8=g+4/8 | | 4(7-n)=5n-8 | | -9.1(-7r-20)=-13 | | 3x=+4=-11 | | 3(y+2+2(y-3=15 | | 2(x5)-8=34 | | 12=y-5/4. | | Z+40=5z | | -9x+3=-10+10 | | -2h+4h=18 | | 120.5=5z. | | 0.15+23=0.19x | | t-7+3t=-2+4t-5 | | 5y-6=y+42 | | -2h+4=18 | | 3n2+7n=20 | | 6n+7=-20 | | 22=4K+7k | | 3i=-21 | | -2v9=25 | | 4x=84. | | -3x+-5=6 | | 12s-45=s+43 | | 460-45x=100 | | 2x-(3x-5)=4(-x-1) | | 6x+4-4x=35-3x-6 | | y-9/4=7. | | Y=6.5x+25 | | -10+21x=-15x+26 | | (½)(6x-8)=41 | | x/3-300=250 |